Business Analysis of KJA Hoven's Carp (Leptobarbus hoevenii) Managed by Bumdes Purnama Kampar, North Kampar Sub District, Riau - Astari, Betri Dea; Darwis, Darwis; Yulinda, Eni (Fakultas Perikanan dan Kelautan Universitas Riau, 2025)
The success of Hoven's carp (Leptobarbus hoevenii) production inputs determines fish farming. One of these production inputs is the availability of seeds for floating net cage cultivation. Hoven's carp are maintained in this KJA, and they are fed twice a day to produce large and healthy Hoven’s carp. Hoven’s carp fish harvest is directly sold to tauke or collectors. This study analyzes the investment, business feasibility, and business constraints of KJA Hoven's carp fish in BUMDes Purnama Kampar. The survey method used 15 respondents using a purposive sampling technique consisting of 1 Director, 1 Secretary, 1 Treasurer, 1 Head of Unit, and 11 Members of BUMDes Purnama Kampar. The types of data collected are primary data and secondary data. Data obtained from interviews, questionnaires, and literature. From the results of research with KJA size 11×4×3.4 (149.6 m3), a total investment of KJA fish business of IDR 718,135,000 was obtained, business revenue of IDR 888,740,000/year, and net profit of IDR 437,971,000 / year. This business is only conducted once a harvest/year. The profit is divided into 50% for BUMDes members and 50% for BUMDes as the business manager. The RCR value of 1.9, FRR of 23.14%, and PPC of 4.3 years indicate that the business is feasible and the capital returns in 4.3 years. The primary constraints are disease attacks, low fish selling prices, and oversupply